SOSIALISASI LITERASI DIGITAL: UPAYA BIJAK MENGGUNAKAN MEDIA SOSIAL PADA PEMUDA-PEMUDI DESA TANJUNG HERAN KECAMATAN PENENGAHAN KABUPATEN LAMPUNG SELATAN - Agus Susanti (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The rapid development of information and communication technology has significantly increased the use of social media across various segments of society, including rural youth communities. While social media provides opportunities for accessing information and expanding social networks, it also poses challenges such as the spread of misinformation, privacy violations, hate speech, and cybercrime. These conditions highlight the importance of strengthening digital literacy through educational activities that promote ethical and responsible social media use. This community service program aimed to provide education for the youth of Tanjung Heran Village, Penengahan District, South Lampung Regency, regarding safe, responsible, and beneficial social media practices. The program employed an interactive socialization approach involving presentations, discussions, and question-and-answer sessions attended by 30 participants. The materials covered personal data protection, digital communication ethics, misinformation prevention, and awareness of cyber threats. The results indicated that participants showed strong enthusiasm, actively engaged in discussions, and demonstrated a better understanding of the importance of maintaining ethical behavior and digital security in social media usage. This activity is expected to serve as an initial step toward strengthening digital literacy among rural youth and fostering a more responsible digital culture within the community.